Islamic Law Based Sociopreneurship in Overcoming Agricultural Distortion and Creating Food Sustainability During the Covid-19 - Syaharuddin,; Awaluddin,; Muntu, Andi Tenri Sri; Raihan, Zulasfiani (LAA MAISYIR : Jurnal Ekonomi Islam, 2023)
The end of 2019 was the beginning of the Corona outbreak, which has now become a serious problem in all aspects of life, including the agricultural sector. One form of innovation initiated by the author is through sociopreneurship in the logistics sector with the name Sepatri (Save Farmers, Save the Country). This research uses a case study type of research with a qualitative approach. The type of data is primary and the data source is through in-depth interviews and observations of affected communities. The research results show that there is a significant impact of the Covid-19 pandemic on farmers and the distribution of agricultural products in Enrekang Regency. The role of sharia-based sociopreneurs in overcoming the problem of distorted distribution of agricultural products has a good role in helping distribute agricultural products in the form of sharia farmer groups as evidenced by the formation of the Women's Farmers Group (KWT) as a forum to help each other from various aspects for the sustainability of living together.